HSP90 pathway in intermediate mononuclear cells causes plaque erosion via induction of neutrophil hyper-responsiveness. (14th October 2021) - Ding, H R; Qian, J; Tong, J; Tang, J N; Lin, H; Chu, J P; Zhu, G Q; Chen, F; Liu, X B
Abstract: Aim: To explore the function(s) of HSP90 in intermediate monocyte-mediated plaque erosion. Materials and methods: We used single-cell RNA sequencing to map cardiac immune response composition in patients with plaque rupture and plaque erosion. By focusing our analyses on CD14 positive monocytes, we obtained a higher resolution identification of the immune cell subsets in patients experiencing plaque erosion and rupture. We interpreted our findings with analyses using gene ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases and by performing receiver operating characteristic (ROC) curve analysis. Results: Single-cell sequencing analysis of mononuclear cells in the peripheral blood of five ACS patients experiencing plaque erosion and rupture confirmed that CD14 positive monocytes were the main immune cells leading to ACS. Interestingly, our results suggested a significant increase in the proportion of atypical monocytes (C4 subsets) in patients with plaque rupture, which was a novel finding. This increase may be caused by increased migration of atypical monocytes into a plaque during plaque rupture. We found that intermediate monocyte activation was most obvious in patients with plaque erosion (C1, C10, and C11), and the proportion of C1 subgroup monocytes (FCGR3B/CMTM2 double strong positive; subsequently defined as intermediate monocytes) was very high. To further explore the role of C1 subgroup intermediate monocytes in plaque erosion, GO and KEGG pathway analyses were performed. GO analysis indicated that C1 subgroup intermediate monocytes are highly involved in neutrophil metabolism. Because neutrophils are the main effector cells that induce plaque erosion, we reasonably infer that intermediate monocytes can induce plaque erosion. KEGG pathway analysis indicated that all subtypes of HSP90 were highly expressed in C1 subgroup intermediate monocytes. We thus collected peripheral blood from ACS patients with plaque rupture (n=150) and plaque erosion (n=150) for mononuclear cell transcriptomics and intracellular proteomics analysis. ROC curve analysis demonstrated that the area under the curve for HSP90-based prediction was 0.86, indicating that HSP90 could be used to predict if patients would experience plaque erosion. Conclusion: Activation of intermediate mononuclear HSP90 expression may be the crucial event that induces neutrophil hyper-responsiveness and leads to plaque erosion. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): China, Shanghai Science and Technology Commission